The translation of Culturemes in the light of the "Language-Culture" dichotomy - MADOUI, Wafa; SI BACHIR, Zina (Journal of Humanities & Social Sciences, 2020)
This article deals with the study of "the translation of Culturemes in the light of the dichotomy "language- culture”, as Culturemes are one of the most important linguistic elements that reflect the socio- cultural context of the texts. This study is based on the analytical- descriptive approach, as we have described the Culturemes and analyzed their different types and classes. We have also discussed the importance of the "language- culture" dichotomy in their translation. The research concluded with a set of results; the most important ones are as follows: - In addition to being linguistic elements, culturemes are considered as symbolic elements carrying a socio- cultural value. - Linguistic analysis alone is not enough to translate the Culturemes. Rather, it is necessary to take into consideration the cultural and civilizational dimension of the texts by carrying out a socio- cultural study in order to penetrate the culture of the Other and transport it to the culture of the Self - The translation of Culturèmes requires a translator with linguistic and anthropological skills.